Synthesis and Antiulcer Activity of 2-[{5-Substituted-1H-benzo(d)imidazol-2-yl sulfinyl}methyl]-3-substituted Phenyl Quinazoline-4(3H)-one Derivatives - Patil, Avinash; Ganguly, Swastika; Surana, Sanjay (Asian Journal of Chemistry, 2010)
The synthesis of 2-[{5-substituted-1H-benzo(d)imidazol-2-yl sulfinyl}methyl]-3-substituted phenyl quinazoline-4(3H)-one derivatives were carried out. Anthranilic acid was treated with chloroacetylchloride to give n-chloroacetyl anthranilic acid (1). 1 was then treated with amines to give 2-chloromethyl-3-aryl-4(3H)-one-quinazoline (2). 2 was condensed with 2-mercapto 5-substituted benzimidazoles 3(a-g), 4(a-g) and 5(a-g) and finally oxidation of sulfur was carried out to give 6(a-g), 7(a-g) and 8(a-g). All compounds were characterized by their spectral studies. Antiulcer activities of 6(a-g), 7(a-g) and 8(a-g) were studied by pylorous ligation induced ulcer models in rats.